Tree functional trait patterns across a chronosequence - Gomes, Aretha Franklin Guimarães (2017)
Understanding the characteristics that allow some species to survive in broader ranges of the ecological succession and how do they vary from those of the other species that are restricted to certain successional stages is an important aspect of ecosystem functioning. To date, few studies proceeded on exploring the differences in the functional traits of generalist and specialist plant species along successional trajectories in neotropical forests. We aim to fill this gap in our study. We investigated generalist and specialist plant species functional traits of three successional stages (early, intermediate and late) in neotropical forests in Reservatório do Funil (Eletrobrás Furnas), Rio de Janeiro state, Brazil. We used five functional traits (specific leaf area, chlorophyll content, resistance to drill, wood density and leaf thickness) to compare generalist and specialist plant species in early, intermediate and late successional stages of a chronossequence. We found evidence that, for generalists species, specific leaf area, chlorophyll content, resistance to drill and leaf thickness values remain constant in all the successional stages. Also, we found that specific leaf area values have no difference in all the successional stages for both generalists and specialists species. There is difference in the chlorophyll content (smaller for early specialists e higher for generalists), resistance to drill (smaller for early specialists and higher on the other stages), wood density (no clear pattern) and leaf thickness (higher on early specialists and lower for intermediate and late specialists). We found that wood density values are similar for early and intermediate specialists. Our results will help guiding the selection for species to be used on forest management and restoration programs.